From “The Snow Child” to “Snow White”: Angela Carter’s inheritance from Classic Fairy Tales - Fan, Yingying; Kaur, Hardev; Ujum, Diana Abu; Mohd Amin, Hasyimah (The Pennsylvania State University Press, 2023)
This article is aimed at developing a Foucauldian power criticism to examine Angela Carter’s inheritance of classic fairy tales. Carter’s “The Snow Child,” inspired by the Grimms’ “Snow White,” has been considered a feminist rewriting in subverting a classic. By establishing a connection between the classic fairy tale “Snow White” and “The Snow Child,” this article examines the two as intertextual in terms of characters and plots, and echoes in the core of subversion as well. With the application of Michel Foucault’s concepts of discipline and punish, the article reveals patriarchy’s operating mechanism in the classic fairy tale—that is, how patriarchy manipulates and tames women. Through punishing the body and disciplining the mind, Carter’s “The Snow Child” explicitly presents the male’s manipulation of power on the female through body production, destiny control, and overt incest, while in the Grimms’ “Snow White,” a hidden clue exposes the operation of the patriarchal power mechanism over women, but in a more subtle way, revealing that patriarchal power disciplines women through brainwashing the mind and punishing the body. Research findings show that rather than being a tool to maintain patriarchal culture, classic fairy tales actually subvert patriarchy implicitly by exhibiting the patriarchy’s operating mechanism in producing “angels.”